A contractual analysis of state versus private ownership - Jiang, Kun; Wang, Susheng (Elsevier, 2017)
We uniquely analyze the advantages and disadvantages of private ownership versus state ownership under various circumstances by focusing on three aspects: external risk, internal governance, and relative importance of owners versus managers. Our theoretical analysis indicates that private ownership is better than state ownership if the business environment is risky, corruption is limited, or the manager plays a more important role than the owner. Our empirical analysis supports our theoretical findings and reveals that better internal governance, more external risk and greater importance of the manager will magnify the benefits of privatization.